Semantic Retrieval With Spreading Activation - Choudhury, Smitashree (2006)
This thesis is mainly concerned with information retrieval with constrained spreading activation in semantic domain of data. Spreading activation has long been a subject of research studies in Artificial Intelligence, cognitive psychological studies. Spreading activation imitates the cognitive aspects of human memory in computational application. In this research we study the effect of spreading activation on a semantic model of data.